2018
DOI: 10.1016/j.knee.2018.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Femoral malrotation from diaphyseal fractures results in changes in patellofemoral alignment and higher patellofemoral stress from a finite element model study

Abstract: Rotational disorders of the distal femur resulted in increased stress on the patellofemoral joint and alignment changes. Malrotation in internal and external rotation might cause patellofemoral pain syndrome from rotations <10°. Care should be taken especially for internal malrotation in the management of femoral shaft fracture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 18 publications
1
11
1
Order By: Relevance
“… 20 , 21 Other biomechanical studies showed that internal rotation of the distal femur resulted in increased patellofemoral contact stress. 22 , 23 , 24 Although the magnitude of rotational changes detected in this present study was low (less than 5° in the majority of the cases) compared to the experimental conditions adopted in those cadaveric studies (10° or 15° increments). The present study has shown that changes in rotational alignment are present after DLO and these issues should be taken into consideration in assessment of the surgical outcomes.…”
Section: Discussioncontrasting
confidence: 54%
“… 20 , 21 Other biomechanical studies showed that internal rotation of the distal femur resulted in increased patellofemoral contact stress. 22 , 23 , 24 Although the magnitude of rotational changes detected in this present study was low (less than 5° in the majority of the cases) compared to the experimental conditions adopted in those cadaveric studies (10° or 15° increments). The present study has shown that changes in rotational alignment are present after DLO and these issues should be taken into consideration in assessment of the surgical outcomes.…”
Section: Discussioncontrasting
confidence: 54%
“…7,8 A recent finite element study reported initiation of significantly higher stresses in the patellofemoral joint at 10°maltorsion. 9 Moreover, previous biomechanical work revealed a significantly higher stress in the knee joint at only 5°maltorsion. 1 In case of existing malalignment leading to clinical complaints, a corrective osteotomy has to be considered to restore the physiological and anatomical relationships.…”
Section: Introductionmentioning
confidence: 94%
“…Another long‐term problem following torsional malalignment of the femur is related to the risk of degenerative osteoarthritis of the knee and/or hip 7,8 . A recent finite element study reported initiation of significantly higher stresses in the patellofemoral joint at 10° maltorsion 9 . Moreover, previous biomechanical work revealed a significantly higher stress in the knee joint at only 5° maltorsion 1 .…”
Section: Introductionmentioning
confidence: 99%
“…With the development of computer science and technology, finite element calculations have been gradually applied widely in the biomechanical research of orthopedics. Recent studies ( 6 8 ) suggest that the fusion of three-dimensional (3D) finite element models and biomechanical models based on images can simulate the stress state of joints more accurately. Brekelmans et al ( 9 ) used this method to preliminarily analyze the influence of vertebral body material properties and geometry on the stress distribution of intervertebral discs.…”
Section: Introductionmentioning
confidence: 99%